Circulating Biomarkers of Collagen Metabolism and Prognosis of Heart Failure with Reduced or Mid-Range Ejection Fraction - Moura Ferreira, Joana; Moura Ferreira, Sara; Joao Ferreira, Maria; Falcao-Pires, Inês (Current Pharmaceutical Design, 2017)
Background: Change in the architecture and composition of cardiac extracellular matrix is a key element in adverse cardiac remodeling that occurs during heart failure. Most of the times, the result is the development of fibrosis, which has a huge impact on the pathophysiology and clinical outcomes of heart failure syndromes. Several molecules related to collagen metabolism detectable in the blood have been proposed as biomarkers of myocardial fibrosis. Despite concerns regarding the true ability of these biomarkers to reflect quantitative and qualitative changes in myocardial collagen, a growing body of evidence suggests that they may play a potential role in several aspects of heart failure management. Methods: This review aimed to summarize published data regarding the role of circulating biomarkers of collagen metabolism in the assessment of prognosis in patients with heart failure with reduced or mid-range LVEF ventricular ejection fraction (LVEF < 40% or LVEF 40-49%, respectively). Medline electronic database was searched to identify relevant studies published through October 2016. Results: Most evidence regarding the prognostic value of collagen biomarkers in HF with reduced or mid-range LVEF lies on data concerning PIIINP and several MMPs and TIMP-1. Several prospective studies found that higher levels of PIIINP, several MMPs and TIMP-1 are associated with higher rates of mortality and/or HF hospital admissions in HF patients with LVEF < 50%. Conclusion: Circulating collagen biomarkers have been shown to play a role in prognostic stratification in heart failure patients with reduced or mid-range ejection fraction.
Keywords: collagen biomarkers